Evaluation of the personnel of the military organizational structure in the performance of their assigned tasks - Kosevtsov , Vyacheslav; Mashtalir , Vadim; Tikhonov , Grigory; Bilyk , Aleksandr (Social Development and Security, 2021)
The article is devoted to the study of the process of assessing the personnel of a military organizational structure in order to increase the capabilities of its personnel in performing the tasks facing it. The article discusses modern scientific trends in determining the personnel assessment system and issues of increasing its efficiency, the main problematic aspects of personnel assessment are formed. The directions for improving the assessment of personnel have been determined, their general characteristics and the ways of its further development have been carried out.